ANÁLISE DAS MUDANÇAS DOS FATORES DETERMINANTES DA ESTRUTURA DE CAPITAL EM FUNÇÃO DO CICLO DE VIDA DAS EMPRESAS BRASILEIRAS SÃO BERNARDO DO CAMPO - REIS, RENATA TOLEDO (2015)
The several theories about the capital structure motivate many studies on this subject, however without meeting a consensus. Other topic not much explored refers to the organization’s life cycle, and how it can influence in the capital structure. This study had as main objective to verify which determinants are the most relevant for the borrowing process in the companies and understand if these determinants change depending on the life cycle, supported by the theories Trade off, Pecking order and Agency’s Theory. In order to achieve the objective was used the analysis of fixed effect panel and Brazilian listed companies have been chosen as sample, finally the study was also based in secondary data available in the Economatica® between 2005 and 2013 using sections from BM&F and BOVESPA. The main result stands the same behavior among the general sample, high and low growth for accounting debt for determining Profitability presenting a negative relationship, and the determinants Growth Opportunity and size, with such a positive relationship. For high groups and some low growth determinants showed different results, such as the uniqueness resulting significance in these two groups, with positive growth in low and negative in the high growth, the collateral value of assets and non-debt tax relief were significant only in low-growth group. For the debt at market value was observed significance for the tax benefit not debt and Singularity. This result reinforces the argument that the life cycle influence the capital structure